Policy Implementation on the Standard Size of Blue Swimming Crab (Portunus spp.) Catched on the East Coast of Lampung - Rizani; Indra Gumay Yudha; Endang Linirin Widiastuti; Novita Tresiana; Indra Gumay Febryano (Journal of Tropical Marine Science, 2026)
The government has issued a policy on the standard size of blue swimming crabs caught to support fisheries management, but it is difficult for business actors to comply with. This study aims to analyze the implementation of the Regulation of the Minister of Marine Affairs and Fisheries No. 7 of 2024 concerning Blue swimming crab Management on the East Coast of Lampung. The research uses a qualitative approach with a case study method, with in-depth interviews, participatory observations, focus group discussions, and documentation studies. The analysis of policy implementation examines fishermen's compliance with the blue swimming crab size standards set by the government. The results of the study show that the cause of the difficulty in implementing the blue swimming crab size provisions is the limited supervision and the lack of sanctions for violations. The orientation of fishermen's behavior still focuses on profits and the limitations of fishing technology that are not selective and destructive. The government must involve all business actors in the trading chain of blue swimming crab commodities to unify perceptions and increase fishermen's understanding of sustainable fisheries management policies on the East Coast of Lampung.